2019
DOI: 10.11591/ijeecs.v16.i2.pp835-842
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-based floor preference for the scheduling of elevators in elevator group control system

Abstract: <p align="JUSTIFY"><span style="font-family: Arial, serif;"><span style="font-size: small;">Modern high-rise buildings require complex yet efficient Elevator Group Control Systems (EGCSs). In vertical transportation through an elevator, a passenger must make a hall call by pressing a landing call button installed at each floor and located near the cars of the elevator group. Conventionally, the EGCS allocates one of the cars for each hall call. Waiting time for the arrival of car and journey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Lift scheduling is a stochastic process as there is always uncertainty about the number of passengers waiting for it and the time at which they will press the hall call button. Sale and Prakash (2019) showed that dynamic approach with time based floor preference in even/odd lifts betters existing lift scheduling system by reducing average passenger waiting time and travel time. Shearn (1983) developed dynamic programming algorithm for scheduling the stops of a single lift where the stops were either predefined or depended on the destination stops of the passengers in it.…”
Section: Related Literaturementioning
confidence: 99%
“…Lift scheduling is a stochastic process as there is always uncertainty about the number of passengers waiting for it and the time at which they will press the hall call button. Sale and Prakash (2019) showed that dynamic approach with time based floor preference in even/odd lifts betters existing lift scheduling system by reducing average passenger waiting time and travel time. Shearn (1983) developed dynamic programming algorithm for scheduling the stops of a single lift where the stops were either predefined or depended on the destination stops of the passengers in it.…”
Section: Related Literaturementioning
confidence: 99%